2018
DOI: 10.3390/sports6040155
|View full text |Cite
|
Sign up to set email alerts
|

Career Termination of Portuguese Elite Football Players: Comparison between the Last Three Decades

Abstract: The aim of this study was to explore the process of career termination of elite soccer players, comparing the quality and the resources to support career termination over the last three decades. To this end, was developed a questionnaire defined by four sections: (a) biographical data, (b) athletic career, (c) quality of career termination and (d) available resources at the moment of career termination. Ninety male former elite Portuguese soccer players participated in this study. The results highlighted a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 15 publications
1
14
1
Order By: Relevance
“…33 Our sample of Portuguese football players retired with a similar age of Kenyan and English footballers, 34,35 earlier than Brazilian footballers/basketball players, 30 but later than other Greek and Spanish elite athletes in different Olympic sports, 11 and the football players in the four major European professional football leagues. 32 The results seem to be in line with the previous research of Carapinheira, Mendes 19 that revealed that the retiring age of Portuguese football players has decreased in the last three decades from 36 to 34 years old. This decrease in the age of retirement cannot be considered positive or negative, because it does not influence the competitive level of retirement.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…33 Our sample of Portuguese football players retired with a similar age of Kenyan and English footballers, 34,35 earlier than Brazilian footballers/basketball players, 30 but later than other Greek and Spanish elite athletes in different Olympic sports, 11 and the football players in the four major European professional football leagues. 32 The results seem to be in line with the previous research of Carapinheira, Mendes 19 that revealed that the retiring age of Portuguese football players has decreased in the last three decades from 36 to 34 years old. This decrease in the age of retirement cannot be considered positive or negative, because it does not influence the competitive level of retirement.…”
Section: Discussionsupporting
confidence: 89%
“…A recent retrospective study with Portuguese international football players also revealed that over the last 10 years, the career path started earlier with an increase in the length of initiation and development stages (increase in the number of years as youth players) and a decrease in the length of the mastery stage (decrease in the number of years as professional players). 19…”
Section: Introductionmentioning
confidence: 99%
“…For athletes, the transition to post‐career is often perceived as a difficult challenge (1), as there is a need to adopt new strategies to ensure that they do not exceed their lower energy requirements. There is a lack of support for former athletes when transitioning to post‐career, which increases susceptibility to develop obesity and other obesity‐related diseases (2).…”
Section: Introductionmentioning
confidence: 99%
“…In Portugal, based on self-reported weight and height, the prevalence of overweight/obesity in former elite athletes is high (~50%) [12], with most athletes report difficulties in managing the end of their career [13], likely due to the lack of support in this transition period. Literature is abundant on the effect of lifestyle interventions targeting individuals with overweight and obesity [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Literature is abundant on the effect of lifestyle interventions targeting individuals with overweight and obesity [14][15][16]. However, former elite athletes are an understudied group and the existence of supportive programs is paramount to improve the quality of their post-career life [3,13]. The promotion of healthy lifestyle programs among inactive former top-level athletes with excess weight is very scarce.…”
Section: Introductionmentioning
confidence: 99%